2015
DOI: 10.1111/hdi.12298
|View full text |Cite
|
Sign up to set email alerts
|

Facial disfigurement due to osteitis fibrosa cystica or brown tumor from secondary hyperparathyroidism in patients on dialysis: A systematic review and an illustrative case report

Abstract: Osteitis fibrosa cystica (OFC) is the most frequent type of osseous change in renal osteodystrophy affecting the majority of dialysis patients. Brown tumors are a severe form of OFC. The involvement of the craniofacial skeleton causing facial disfigurement in patients on dialysis appears to be limited to case reports. After searching PubMed, we performed a systematic review of 127 cases with a severe form of OFC resulting in a facial disfigurement to understand possible determinants for this condition. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
0
19
0
2
Order By: Relevance
“…The tumors are soft and brownish in color due to episodes of hemorrhages from microfractures of the thinned and demineralized bone. They present as either single or multiple lesions and are destructive by their lytic and expansive properties [ 5 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tumors are soft and brownish in color due to episodes of hemorrhages from microfractures of the thinned and demineralized bone. They present as either single or multiple lesions and are destructive by their lytic and expansive properties [ 5 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…More than one-third (35.4 %) of brown tumor cases have symptomatic improvement at follow-up. The mean follow-up duration was 1.6 years [30]. The only method for treating primary hyperparathyroidism is the surgical removal of the parathyroid adenoma or adenomas [31].…”
Section: Discussionmentioning
confidence: 99%
“…16 Furthermore, our study identified a female preponderance, consistent with the literature, in what has been speculated to be a consequence of women's lower body mass, which would lead to an earlier clinical manifestation of the disease. 17,18 BTH may clinically present as either a painful exophytic mass or as an asymptomatic swelling, causing a well-defined radiolucent or hypodense image on radiographic and CT examinations but usually not producing cortical disruptions and periosteal reactions. 19,20 As found in this series, multifocal lesions may also be present.…”
Section: Discussionmentioning
confidence: 99%